Readiness of Special-Needs Schools in Developing Oral Language Skills Programs for Deaf Students - Imas Diana Aprilia (The Center for Disability Studies and Services Brawijaya University, 2021)
Limited learning programs in developing spoken language, as well as the inconsistency of teachers in implementing oral language communication, are allegedly the main causes of poor communication skills, especially for hearing impaired students. In contrast to this, oral language skills are a prerequisite for having communication with others. The present study draws attention to receive a description of the school (teacher) readiness in developing oral language skills programs for students with hearing impairment. Conducted through descriptive qualitative method, the current project explores data from the chosen teachers of grade 2, 3, and 4, as well as PKPBI teachers through interviews, observation and documentation study. The data analysis technique is performed through data reduction, data presentation, drawing conclusions and verification. The findings disclosed that the oral language program planning is based on incidental needs analysis. The oral language skills program is still developed separately from the PKPBI program and communication training (either speaking or articulation). Likewise, conversational competence as a basis for developing communication has not become a definite program and is only applied to certain themes. The implementation of the oral language skills program is carried out partially with different learning patterns and methods, namely the global word method and the maternal reflective method (MMR).Â The teacher's evaluation was limited to correcting phonemes, repeating simple sentences and once into integrated thematically. The faced constraints are the availability of supporting infrastructure such as PKPBI room and articulation room that have not been optimized and the limited number of speech experts and PKPBI teachers. For such obvious reason, the seriousness and consistency of schools are highly necessary in developing oral language skills programs as the main focus during the learning process at each grade level by providing opportunities for all teachers to possess integration with PKPBI program and thematic articulation training programs using the reflective maternal method (MMR).